048 Heavy shoulder strengthening exercises in patients with hypermobility and long-lasting shoulder symptoms: a feasibility study. (3rd March 2020) - Liaghat, Behnam; Skou, Søren T; Jørgensen, Uffe; Sondergaard, Jens; Søgaard, Karen; Juul-Kristensen, Birgit
Abstract : Background: Patients with hypermobility spectrum disorder (HSD) are in great risk of experiencing shoulder symptoms, but evidence for exercise as treatment is sparse. Objective: To evaluate the feasibility of heavy shoulder strengthening exercise in patients with HSD and long-lasting shoulder symptoms. Design: Feasibility study. Setting: Primary care. Patients (or Participants): Twelve patients (39.3±13.9 years) with HSD and shoulder instability and/or pain >3 months. Interventions (or assessment of risk factors): 16-week progressive heavy shoulder strengthening programme 3 times/week using exercises targeting scapular and rotator cuff muscles. Main outcome measurements: Pre-defined progression criteria included recruitment rate (acceptable: 6 patients/month), test duration (acceptable: <120 min), patient retention (acceptable: >80% complete intervention), training adherence (acceptable: >75% adhere to >36 training sessions), adverse events (acceptable: minor events with no patients discontinuing the study), besides patient and physiotherapist feedback. Treatment outcomes were assessed using patient-reported health parameters, such as the Western Ontario Shoulder Instability Index (WOSI (0–2100, better to worse)), outcomes on pain, fatigue and kinesiophobia, besides isometric shoulder strength and clinical tests (shoulder instability, hypermobility and proprioception). Results: Recruitment rate was 5.6/month, assessment duration (mean±SD) 105±9 min, retention 100%, adherence 83%, and four patients experienced short-lasting soreness/pain. Patient feedback was positive, and physiotherapists found the intervention relevant and applicable to the patient-group. WOSI total score improved by 51% (mean±SD, points: baseline 1037±215; follow-up 509±365; mean change (95% CI), 528 (318; 738)), and patients reported reduced pain, fatigue and kinesiophobia. Shoulder strength measurements improved by 28–31% (mean change (95% CI), Nm/kg: scaption 0.51 (0.23; 0.78); internal rotation 1.32 (0.70; 1.95); and external rotation 0.89 (0.37; 1.40)). Clinical tests indicated increased shoulder stiffness. Conclusions: The shoulder strengthening programme was feasible in patients with HSD and long-lasting shoulder symptoms. A future randomised controlled trial, with an improved recruitment strategy, will demonstrate whether the exercise programme is effective in improving symptoms in this patient group.